Diminutiver på -ke i danske personnavne - Birgit Eggert (Nordisk Tidskrift för Socioonomastik)
This study shows how during the Middle Ages, names in Denmark originally formed using the diminutive -ke are more frequent in male names than female names. In contrast, -ke was far more frequent in female names during the 18th century, compared to male names. Perhaps by this time names ending in -ke had begun to be perceived as feminine names. Furthermore, geographical distribution had changed considerably by the 18th century, and the majority of the name bearers were found in rural areas and, not mainly in market towns and Southern Jutland as was the case in the Middle Ages. This may indicate that the medieval use of names ending in -ke among German migrants had integrated with local Danish naming and had moved from towns to the rural population.